Between Night and Night ... - Cassidy, Bonny (RMIT University, 2024)
Background: This review essay discusses the Australian poet, Peter Boyle, in the contexts of the long poem and ecopoetics. It considers how Boyle’s poetics demonstrates the impact of his late partner, anthropologist Deborah Bird Rose. This essay engages with my substantial record of scholarly and critical publications of Australian poetry and ecocriticism, as well as my creative practice as the author of a book-length poem, Final Theory (2014) concerned cosmology and colonisation. Contribution: In ‘Between Night and Night’ I use the review essay to make a transdisciplinary link between Boyle’s recent book-length poem, Enfolded in the Wings of a Great Darkness, and work of Bird Rose by incorporating images from her writing as well as concepts of animism. Since other reviews of Boyle’s works associate him with French, Spanish and Latin American surrealism and metafictional voice, this is a new way of approaching Boyle’s work. It also adds to discourse on the interplay between First Nations philosophy and ...